2014
DOI: 10.1155/2014/575184
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Lose Weight from the Perspective of Children with Overweight/Obesity and Their Parents: A Sociocultural Approach

Abstract: Introduction. There are not enough studies about the barriers to lose weight from the perspective of children and their parents. Methods. Children and adolescents diagnosed with overweight/obesity in the Department of Endocrinology and their parents were invited to participate in a series of focus group discussions (FGD). Twenty-nine children 10–16 years old and 22 parents participated in 7 focus groups; 2 mothers and 2 adolescents participated in depth interviews. All interviews were recorded, transcribed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 38 publications
0
30
0
10
Order By: Relevance
“…The same study reported that as little as 15 min of MVPA may have some positive effects on adiposity among children. Given that lack of time is a barrier to physical activity among this population group, 15 min bouts of MVPA could be a more realistic, achievable target to help preventing childhood obesity.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The same study reported that as little as 15 min of MVPA may have some positive effects on adiposity among children. Given that lack of time is a barrier to physical activity among this population group, 15 min bouts of MVPA could be a more realistic, achievable target to help preventing childhood obesity.…”
Section: Discussionmentioning
confidence: 81%
“…A series of analysis were therefore conducted by sequentially omitting one study at each turn. Finally, a stratified exploratory analysis was performed using the same procedures as the main analysis comparing the time blocks exchanged (15,30 or 60 min).…”
Section: Data Synthesis and Analytical Approachmentioning
confidence: 99%
“…Many studies reported that parents do not correctly identify their children’s weight status with the percentage of misclassification ranging from 20% to 80% [ 3 , 15 , 16 , 19 , 21 , 29 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In a Canadian study, 63% of parents classified their children as normal weight when in fact, they were overweight [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 In Mexico Ana et al, in 2014 found that parents of obese children visit the hospital only with obesity complications. 12 They do not consider overweight a health problem. Regarding health care providers, although the values of weight, height and BMI are available in all patients' files by default, general weight counseling was not a routine practice in the visits of most patients if weight was in the normal range, general weight counselling was found in only 2 files from total of 817 files (0.2%) with normal weight.…”
Section: Discussionmentioning
confidence: 99%